The Effect of Flashcard Media with Local Wisdom of Jepara on Students' Socio-Cultural Character - Fajrie, Nur; Fivtia Sari , Ninis; Ramli, Muhamad Firdaus; Sa’diyah , Isnaini Khalimatus (Universitas Negeri Semarang, 2024)
This study aims to determine the effect of the socio-cultural character of 4th-grade students of SD N 3 Banyumanis before and after using flashcards with Jepara local wisdom and how much the effect is. This research is quantitative. The experimental research design used was the Pre-experimental One Group Pretest-Posttest Design. This research was conducted on grade 4 students at SD N 3 Banyumanis with 22 students. The data in this study were collected using a questionnaire. The data will be analyzed using the T-test. Based on the data obtained, the average value can be seen from the average value, where the pretest obtained an average score of 226.13 while the post-test obtained an average score of 235.36. Then, e T-test obtained a significance value of 0.000 <0.05. So, Ha is accepted, and H0 is rejected, which means that there is an effect of using flashcards based on Jepara local wisdom to improve socio-cultural character in grade 4 SD N 3 Banyumanis.